2021
DOI: 10.1111/mpp.13093
|View full text |Cite
|
Sign up to set email alerts
|

Cotton GhSSI2 isoforms from the stearoyl acyl carrier protein fatty acid desaturase family regulate Verticillium wilt resistance

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 90 publications
2
19
0
Order By: Relevance
“…Compared with the WT, more resistance genes were activated in GhENODL transgenic plants, and KEGG revealed phenylpropanoid biosynthesis was enriched ( Figure 7 b). Given the fact that the phenylalanine ammonia lyase pathway is the main synthesis pathway of SA in cotton [ 35 ] and the results of qPCR in Figure 4 e and the RNA-seq data, we deduced that GhENODL6 is probably involved in SA signaling. Thus, the SA pathway-regulated genes, EDS1, PR1, PR2, PR5, and PR10 , were detected via qPCR ( Figure 8 a–e).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Compared with the WT, more resistance genes were activated in GhENODL transgenic plants, and KEGG revealed phenylpropanoid biosynthesis was enriched ( Figure 7 b). Given the fact that the phenylalanine ammonia lyase pathway is the main synthesis pathway of SA in cotton [ 35 ] and the results of qPCR in Figure 4 e and the RNA-seq data, we deduced that GhENODL6 is probably involved in SA signaling. Thus, the SA pathway-regulated genes, EDS1, PR1, PR2, PR5, and PR10 , were detected via qPCR ( Figure 8 a–e).…”
Section: Resultsmentioning
confidence: 78%
“…SA is a key defense-related hormone in plants, which plays an important role in SAR and broad-spectrum durable disease resistance Among the reported plant defense hormones, the roles of SA, JA, and ethylene (Eth) have been established, and these hormones play important roles in biological stress signaling pathways, including ROS and MAPK kinases [8]. In cotton, most SA biosynthesis relies on the phenylalanine ammonia lyase pathway [35]. In this study, according to qPCR results and RNA-seq data, we inferred that GhENODL6 could activate the phenylpropanoid pathway and promote SA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our previous iTRAQ-based quantitative proteomic study showed a more significant accumulation of PAL protein (Cla008727) in pumpkin rootstock-grafted than self-grafted watermelon plants after exposure to chilling for 48 h [ 45 ]. The virus-induced gene silencing of PAL in cotton plants showed reduced levels of both free SA and SAG content, suggesting that the SA biosynthesis is critically dependent on the PAL pathway [ 46 ]. Many chemical modifications of SA can occur in cells, and glucose conjugation at the hydroxyl group of SA leads to the biosynthesis of inactive SAG which is stored in the vacuolar [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A moisturizing transparent high cover was used to protect the pots for 24 h to prevent evaporation. The necrotic spots in the leaves were observed with trypan blue staining [ 85 ]. Plants treated with 10 μM TA were prepared for protein extraction because this concentration of TA effectively induced a leaf response.…”
Section: Methodsmentioning
confidence: 99%